L'accord monétaire de Maastricht et ses implications de politiques économiques - Nyahoho, Emmanuel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1993)
The precised calendar of Maastricht treaty for setting up the european System of central banks (ESCB) and the european central bank (ECB) with a single currency can merely be explained by the concern of the member countries of having such a monetary integration before the end of the century. There's every chance that ESCB be formed with limited number of countries, namely: France, Germany, Luxembourg, Netherlands. If the objectives of price controls and non monetisation of debt assigned to ESCB are unequivocal, the responsability of fixing the parity of écu vis-à-vis third currencies which belongs to the Council and the Parliament might deprive the ESCB of full scope in conducting monetary policy. In regard to fiscal policies, the coexistence of budgets of various natures and the conjonctural stabilizations programs in prospect render difficult any computation on future coordination policy or federal budget. Finally, ecu once in place as a single currency could extend beyond the communities, but its acceptance on financial and commercial markets beside the dollar and the yen is scarcely predictable. This tendancy toward currencies zone, thus repeating history of the years thirties, does not constitute any guaranty for the stability of international monetary System which would require a kind of multilateral surveillance.